Uncovering systemic barriers related to equity, diversity and inclusion in child health research: a scoping review addressing marginalised communities - Aleem Bharwani; Nicole Johnson; Ulises Charles-Rodriguez; Deliwe P Ngwezi; Suha Damag; Tehseen Ladha; Oluwabukola Salami (BMJ Global Health)
Introduction Despite abundant evidence illustrating the impact of social determinants of health on children and youth from marginalised communities, their continued marginalisation in research contributes to a negative feedback loop that perpetuates health inequities. Previous reviews have identified barriers in marginalised adult communities. However, no comprehensive review outlines the scope of barriers to equity, diversity and inclusion (EDI) in child health research across multiple marginalised communities, particularly as they are defined in Canada.Methods The purpose of this review is to scope and summarise research discussing systemic barriers influencing EDI in child health research, focusing on racialised and black individuals, 2SLGBTQIA+ individuals, Indigenous peoples, women and girls and individuals with disabilities (identified as priority communities in the Canadian government’s research policy). Our team followed the steps proposed by Arksey and O’Malley for scoping reviews.Results From 3336 identified records, 53 publications met the inclusion criteria. Most studies were based in the USA (n=40) and/or other English-speaking countries (n=14), emphasising the need for global perspectives. Some publications were based in more than one country; others addressed more than one marginalised community. We identified more publications discussing racialised individuals (n=30) and black individuals (n=20) than women and girls (n=10), Indigenous peoples (n=9), children with disabilities (n=7) or 2SLGBTQIA+ individuals (n=4). Publications increased from 3 in 2020 to 15 in 2022, reflecting heightened awareness of structural racism and health inequities during the COVID-19 pandemic. Our findings suggest systemic under-recruitment and tokenism. Other factors in the research ecosystem include misleading conceptualisations of race and other social categories, power dynamics, lack of cultural safety and discrimination. Finally, we recommend applying the socio-ecological model to systematically map barriers and develop tailored, multilevel solutions that promote equity and inclusivity in research.Conclusion To foster a more equitable and impactful child health research ecosystem, institutions must address individual, interpersonal, organisational and policy-level barriers by embedding community-driven priorities, promoting diverse and inclusive practices, and ensuring long-term, reciprocal relationships with historically marginalised communities.